Perceived Burdensomeness and the Wish for Hastened Death in Persons With Severe and Persistent Mental Illness - Stoll, Julia; Ryan, Christopher James; Trachsel, Manuel (Frontiers in Psychiatry, 2021)
Background: In several countries in Europe, medical assistance in dying (MAID) is no longer limited to persons with a terminal prognosis, but is also available to those who suffer from lasting and unbearable mental illness. So far, the scholarly discourse on MAID in this population has been dominated by issues such as decision-making capacity, the uncertainty of when a disease is incurable, stigmatization, isolation, and loneliness. However, perceived burdensomeness has been given little attention. Objective: We explore the possible impact of perceived burdensomeness on the request for MAID in persons with severe and persistent mental illness (SPMI). Method: Using the method of ethical argumentation, we discuss the issue of access to MAID for persons with SPMI and perceived burdensomeness. Conclusion: Perceived burdensomeness may be a contributing factor in the wish of persons with SPMI for hastened death. MAID is ethically unsupportable if persons, due to their SPMI, make estimates of their burdensomeness that are unrealistic and who therefore, lack decision-making capacity relevant to the MAID request. However, the possibility that some individuals with SPMI may perceive burdensomeness doesn’t mean that they should be routinely excluded from MAID. Moreover in patients with preserved decision-making capacity who suffer SPMI that perceive their lives to be not worth living, perceived burdensomeness – if it is a component of this intolerable suffering – is not a sufficient reason to deny the patient access to MAID.